Concordance and agreement between different activity scores in polymyalgia rheumatica - Bruno Fautrel; Eric Toussirot; Renaud Felten; Emmanuel Nowak; Christophe Richez; Jacques-Eric Gottenberg; Isabelle Chary-Valckenaere; Alain Saraux; Aleth Perdriger; Emanuelle Dernis; Thierry Marhadour; Marie-Elise Truchetet; et al. (RMD Open)
Objective The C reactive protein polymyalgia rheumatica activity score (CRP-PMR-AS) is a composite index that includes CRP levels and was developed specifically for PMR. As treatments such as interleukin-6 antagonists can normalise CRP levels, the erythrocyte sedimentation rate (ESR) of PMR-AS, the clinical (clin)-PMR-AS and the imputed-CRP (imp-CRP)-PMR-AS have been developed to avoid such bias. Our primary objective was to measure the correlation of these activity scores. Our secondary objective was to evaluate the concordance between different cutoffs of the PMR-ASs.Method Data from the Safety and Efficacy of tocilizumab versus Placebo in Polymyalgia rHeumatica With glucocORticoid dEpendence (SEMAPHORE) trial, a superiority randomised double-blind placebo-controlled trial, were subjected to post hoc analysis to compare the efficacy of tocilizumab versus placebo in patients with active PMR. The CRP-PMR-AS, ESR-PMR-AS, clin-PMR-AS and imp-CRP-PMR-AS were measured at every visit. The concordance and correlation between these scores were evaluated using kappa correlation coefficients, Bland-Altman correlations, intraclass correlation coefficients (ICCs) and scatter plots.Results A total of 101 patients were included in the SEMAPHORE trial, and 100 were analysed in this study. The correlation between the PMR-ASs was excellent, as the ICC and kappa were >0.85 from week 4 until week 24 (CRP-PMR-AS ≤10 or >10). Bland-Altman plots revealed that the differences between the CRP-PMR-AS and the other threescores were low. The cut-off values for the clin-PMR-AS were similar to those for the CRP-PMR-AS 86% of the time.Conclusion The correlation between all the PMR-ASs was excellent, reflecting the low weight of CRP. In clinical trials using drugs that have an impact on CRP, the derived activity scores can be used.Trial registration number NTC02908217.